An Analysis of Thaumarchaeota Populations from the Northern Gulf of Mexico - Tolar, Bradley B.; King, Gary M.; Hollibaugh, James T. (Frontiers in Microbiology, 2013)
We sampled Thaumarchaeota populations in the northern Gulf of Mexico, including shelf waters under the Mississippi River outflow plume that are subject to recurrent hypoxia. Data from this study allowed us to: 1) test the hypothesis that Thaumarchaeota would be abundant in this region; 2) assess phylogenetic composition of these populations for comparison with other regions; 3) compare the efficacy of quantitative PCR (qPCR) based on primers for 16S rRNA genes (rrs) with primers for genes in the ammonia oxidation (amoA) and carbon fixation (accA, hcd) pathways; 4) compare distributions obtained by qPCR with the relative abundance of Thaumarchaeota rrs in pyrosequenced libraries; 5) compare Thaumarchaeota distributions with environmental variables to help us elucidate the factors responsible for the distributions; 6) compare the distribution of Thaumarchaeota with Nitrite-Oxidizing Bacteria (NOB) to gain insight into the coupling between ammonia and nitrite oxidation. We found up to 108 copies L-1 of Thaumarchaeota rrs in our samples (up to 40% of prokaryotes) by qPCR, with maximum abundance in slope waters at 200-800 m. Thaumarchaeota rrs were also abundant in pyrosequenced libraries and their relative abundance correlated well with values determined by qPCR (r2=0.82). Thaumarchaeota populations were strongly stratified by depth. Canonical correspondence analysis using a suite of environmental variables explained 92% of the variance in qPCR-estimated gene abundances. Thaumarchaeota rrs abundance was correlated with salinity and depth, while accA abundance correlated with fluorescence and pH. Correlations of Archaeal amoA abundance with environmental variables were primer-dependent, suggesting differential responses of sub-populations to environmental variables. Bacterial amoA was at the limit of qPCR detection in most samples. NOB and Euryarchaeota rrs were found in the pyrosequenced libraries; NOB distribution was correlated with that of Thaumarchaeota (r2=0.49)